Bridging the gap: Early detection of pulmonary tuberculosis among PLHIV in Western Rajasthan, India - Aditi Gupta; Ravisekhar Gadepalli; Vidhi Jain; Kumar S. Abhishek; Nishant Kumar Chauhan; Deepak Kumar (Lung India)
Background: Tuberculosis (TB) remains a leading cause of mortality among people living with HIV (PLHIV), with delayed diagnosis contributing significantly to poor outcomes. Early detection through systematic screening and diagnostic tools is essential to reduce morbidity and mortality in this high-risk population. This study aimed to evaluate the utility of the World Health Organization (WHO) four-symptom screen (fever, cough, weight loss, and night sweats), using Xpert MTB/RIF (Cepheid, Sunnyvale, California) as the gold standard for early detection of pulmonary TB in HIV-positive patients. Methods: A total of 249 HIV-positive patients attending a tertiary care centre in Western India were screened using the WHO four-symptom tool. All patients, regardless of symptoms, underwent testing with Xpert MTB/RIF. Sensitivity, specificity, and predictive values were calculated for the symptom screen and individual symptoms. Univariate and multivariate analysis was performed to determine significance (P < 0.05). Results: The WHO four-symptom screen identified 40.2% of participants (n = 100) as screen-positive. Xpert MTB/RIF confirmed pulmonary TB in 5.6% (n = 14) of the total population. The combined sensitivity and specificity of the WHO symptom screen were 85.7% and 62.6%, respectively, with a high negative predictive value of 98.7%. Fever and cough were the most significant predictors (P < 0.05) in multivariate analysis. Conclusion: The study highlights the importance of systematic TB screening among PLHIV using the WHO symptom tool in conjunction with molecular diagnostics. This approach facilitates early diagnosis and treatment, contributing to better health outcomes and aligns with global TB elimination strategies.